Implications of perceived empathy from spouses during pregnancy for health-related quality of life among pregnant women: a cross-sectional study in Anhui, China - Yu Zhu; Ting Zhu; Hui Wang; Ji-Min Zhu; Dan-dan Zheng; Ping Yin; Bai-Kun Li (BMC, 2024)
Abstract Background Empathy is a critical component of nursing care, impacting both nurses' and patients' outcomes. However, perceived empathy from spouses during pregnancy and its impact on health-related quality of life (HRQoL) are unclear. This study aimed to examine pregnant women's perceived empathy from their spouses and assess the relation of perceived empathy on HRQoL. Methods This cross-sectional study, performed in the obstetric clinics or wards of four well-known hospitals in Anhui Province, China, included 349 pregnant women in the second or third trimester; participants were recruited by convenience sampling and enrolled from October to December 2021. A general information questionnaire, the Interpersonal Reactivity Index (IRI), a purpose-designed empathy questionnaire and the Medical Outcomes Study 12-item Short-Form Health Survey (SF-12) were used to evaluate the pregnant women's general information, perceptions of empathy and HRQoL. Data were analysed using SPSS 22 at a threshold of P < 0.05. Descriptive analysis, Pearson correlation analysis, Student's t test, ANOVA, and multiple regression analysis were used for analysis. Results The pregnant women's total empathy, physical component summary (PCS) and mental component summary (MCS) scores were 41.6 ± 9.0, 41.6 ± 7.6, and 47.7 ± 9.1, respectively. Correlation analysis revealed that the purpose-designed empathy questionnaire items were significantly positively correlated with perspective taking and empathic concern but were not correlated with the personal distress dimension and were only partially correlated with the fantasy dimension. Maternal physical condition during pregnancy, planned pregnancy, and occupational stress were predictors of the PCS score (β = 0.281, P < 0.01; β = 0.132, P = 0.02; β = -0.128, P = 0.02). The behavioural empathy item of our purpose-designed empathy questionnaire and empathic concern were important predictors of the MCS score (β = 0.127, P = 0.02; β = 0.158, P < 0.01), as well as other demographic and obstetric information, explaining 22.0% of the variance in MCS scores totally (F = 12.228, P < 0.01). Conclusions Pregnant women perceived lower empathy from their spouses and reported lower HRQoL. Perceived empathy, particularly behavioural empathy, may significantly impact pregnant women's MCS scores but has no effect on their PCS scores. Strategies that foster perceived empathy from spouses among pregnant women are essential for facilitating healthy pregnancies and potentially improving maternal and child health.